Features of physical preparedness of skilled sportsmen which are specialized in jumps disciplines of track-and-field. - Bobrovnik V.I; Krivoruchenko O.V (Kharkov National Pedagogical University, 2010)
Outcomes of survey of sportsmen of a reserve combined team of Ukraine are indicated. 81 sportsman has taken part in testing. Age of sportsmen - 17-22 years. The estimation of a level of physical readiness of jumpers in length, in height, with the sixth, threefold (men and women) is conducted. Idiosyncrasies of physical readiness of jumpers are revealed depending on sports specialization. In training process lacks which brake development of impellent qualities of sportsmen are defined. Ways of removal of these lacks are offered.